Galloway-Maxcy-Markoe families papers - Galloway, John, -1810.; Galloway, Samuel, 1720-1785.; Markoe, Francis, 1801-1871.; Maxcy, Virgil, 1785-1844.
Correspondence, business papers, financial records, legal documents, speeches, reports, essays, memoranda, and other papers relating to commerce and economic conditions in Maryland (1750-1810) and foreign affairs and political events in the 1840s and 1850s. Documents Virgil Maxcy's position as American chargé de'affaires in Brussels, 1837-1842; Francis Markoe's career in the State Department and as corresponding secretary of the National Institute for the Promotion of the Sciences; the institute's mineralogical collection; trade with England especially the London firm, Higginson & Bird; and tax levies in Anne Arundel County, Md., 1764-1765. Includes the manuscript of Virgil Maxcy's biography of John C. Calhoun and numerous letters from Calhoun.
Other correspondents include J.J. Albert, Lewis Cass (1782-1866), Lewis Cass (b. 1808), George Mifflin Dallas, Albert Davy, Daniel Dulany, Peter Force, Alexander Hamilton, David Hoffman, George W. Hughes, Charles Jared Ingersoll, Joseph R. Ingersoll, James Kent, David Lynn, Francis Scott Key, George McDuffie, John Francis Mercer, James Monroe, Joel Roberts Poinsett, Richard Rush, Joseph Story, Thomas Swann, Samuel Swartwout, Roger Brooke Taney, Benjamin Tasker, George Washington, and Daniel Webster. Correspondents also include members of the Cheston, Chew, Howard, and Tilghman (Tillman) families.
Microfilm edition of the Higginson & Bird letterbook available
Members of the Galloway, Maxcy (Maxey), and Markoe families represented include Samuel Galloway and his son, John, merchants; John's son-in-law, Virgil Maxcy, lawyer, politician, and diplomat; and Virgil's son-in-law, Francis Markoe, public official.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Albert, J. J. -- Correspondence; Calhoun, John C. -- 1782-1850.; Calhoun, John C. -- 1782-1850 -- Correspondence; Cass, Lewis, -- 1782-1866 -- Correspondence; Cass, Lewis, -- 1808-1878 -- Correspondence; Dallas, George Mifflin, -- 1792-1864 -- Correspondence; Davy, Albert -- Correspondence; Dulany, Daniel, -- 1722-1797 -- Correspondence; Force, Peter, -- 1790-1868 -- Correspondence; Hamilton, Alexander, -- 1786-1875 -- Correspondence; Hoffman, David, -- 1784-1854 -- Correspondence; Hughes, George W. -- 1806-1870 -- Correspondence; Ingersoll, Charles Jared, -- 1782-1862 -- Correspondence; Ingersoll, Joseph R. -- 1786-1868 -- Correspondence; Kent, James, -- 1763-1847 -- Correspondence; Lynn, David, -- 1758-1835 -- Correspondence; Key, Francis Scott, -- 1779-1843 -- Correspondence; McDuffie, George, -- 1790-1851 -- Correspondence; Mercer, John Francis, -- 1759-1821 -- Correspondence; Monroe, James, -- 1758-1831 -- Correspondence; Poinsett, Joel Roberts, -- 1779-1851 -- Correspondence; Rush, Richard, -- 1780-1859 -- Correspondence; Story, Joseph, -- 1779-1845 -- Correspondence; Swann, Thomas, -- 1805-1883 -- Correspondence; Swartwout, Samuel, -- 1783-1856 -- Correspondence; Taney, Roger Brooke, -- 1777-1864 -- Correspondence; Tasker, Benjamin, -- 1720-1760 -- Correspondence; Washington, George, -- 1732-1799 -- Correspondence; Webster, Daniel, -- 1782-1852 -- Correspondence; Cheston family -- Correspondence; Chew family -- Correspondence; Galloway family; Howard family -- Correspondence; Maxey family; Markoe family; Tillman family -- Correspondence; United States. -- Department of State; Higginson & Bird; National Institute for the Promotion of the Sciences; Diplomatic and consular service, American -- Belgium; Minerals -- Catalogs and collections; Science -- United States; Taxation -- Maryland -- Anne Arundel County; Belgium -- Foreign relations -- United States; England -- Commerce -- Maryland; Maryland -- Commerce -- England; Maryland -- Commerce; Maryland -- Economic conditions; Maryland -- Politics and government -- 1775-1865.; United States -- Foreign relations -- 1783-1865.; United States -- Foreign relations -- Belgium; United States -- Politics and government -- 1815-1861.